(untitled) - Daniel Baier, University of Bayreuth, Germany; Yasemin Boztug, University of Goettingen, Germany; Heribert Gierl, University of Augsburg, Germany; Andrea Gröppel-Klein, Saarland University, Germany; Lutz Hildebrand, Humboldt-University of Berlin, Germany; Joerg Koenigstorfer, Technical University of Munich, Germany; Martin Klarmann, Karlsruhe Institute of Technology (KIT), Germany; Hans Mühlbacher, University of Monaco, Principality of Monaco; Henrik Sattler, University of Hamburg, Germany; Bernhard Swoboda, University of Trier, Germany; Dirk Temme, University of Wuppertal, Germany; Udo Wagner, Modul University Vienna, Austria; et al. (Marketing ZFP, 2005)
Marketing ZFP is a platform for the academic dialog between marketing science and marketing practice. It offers critical depictions of the newest developments in the central areas of marketing science and marketing practice. Thereby, Marketing ZFP dedicates itself particularly to the transfer of methodological knowledge into practice.Articles published in Marketing ZFP are peer-reviewed and written in either German or English. English abstracts are available for all articles.The scientific quality of Marketing ZFP has been ranked highly: In the VHB-JOURQUAL Ranking of the German Association for Business Research, the journal is listed among the top five German journals in business research. In GeMark, the German Marketing-Journal Ranking, it is listed in category B.For more information for authors and subscribers, see www.marketing-zfp.de.